Photochemistry and Structure of Aromatic Azo Compounds Isolated in Cryogenic Noble-Gas Matrices - Duarte, Luís (2014)
Tese de doutoramento em Química, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra